Fatal SARS in X-Linked Lymphoproliferative Disease Type 1: A Case Report - Chung, Ming Hin; Chua, Gilbert T.; Leung, Daniel; Chan, Koon Wing; Nicholls, John; Lau, Yu Lung (Frontiers in Pediatrics, 2022)
X-linked lymphoproliferative disease (XLP1) is an inborn error of immunity (IEI) with severe immune dysregulation caused by a mutation in the SH2D1A gene resulting in the absence or dysfunction of signalling lymphocytic activation molecules (SLAM)-associated protein (SAP). The severe acute respiratory syndrome (SARS) caused by SARS-CoV, a highly pathogenic coronavirus, has been shown to only cause mild diseases in Asian children. We report a 5-year-old Nepalese boy with agammaglobulinemia and probable SARS, died of diffuse alveolar damage 22 days after admission amid the SARS outbreak. The index patient and his younger brother were genetically confirmed to have XLP1. In the current coronavirus disease 2019 (COVID-19) pandemic, most children also had mild disease only. Children with severe COVID-19 diseases would warrant investigations for underlying IEI, particularly along the pathways leading to immune dysregulation.